A STUDY OF THE PATTERN OF CASTEWISE PARTY REPRESENTATION IN VIDHAN SABHA ELECTIONS IN VIDARBHA - 2009-2019 - Dr.Rahul Bavge, Dr.Aseem Khapre, Dr.Sandip Tundurwar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Caste is an undeniable reality in Indian Social-Political Life. Various factors such as political process, voting, candidature, composition of council of Ministers are compulsorily and irrevocably affected by caste. Castewise reservation was given in post-independence era for the transformation of political democracy into social democracy. All political parties claim to be all inclusive. They try to get support of all castes and relgions in order to get elected and to continue the acquired power. The present paper has tried to shed light on social representation of various political parties in last three Vidhan Sabha Elections in Vidarbha Region of Maharashtra State in India. It also tries to understand social mass basis of political parties and different communities’ priority of political parties. Need of study: The social mass base of political parties need to be strong in order to win elections and preserve the acquired power in Indian democracy. During last nine Vidhan Sabha elections in Maharashtra from 1990 to 2019, no single political party has got majority. As such political parties have been forced to make alliances to form government. Whether somebody wishes to do so or not, following the obligation of alliance-government has become political need in Maharashtra. The public voted for change of power in the 1995, 1999, 2014 and 2019 elections. The changing social mass base and representation of political parties is responsible to a large extent for these frequent changes in power. Thus study is necessary to understand this phenomenon.